trans-Resveratrol, an extract of red wine, inhibits human eosinophil activation and degranulation - Tan, Y (Nature Publishing Group, 2008)
BACKGROUND AND PURPOSE: trans-Resveratrol, a non-flavonoid polyphenol found abundantly in red wine possesses antiproliferative and anti-inflammatory activity in various inflammatory disease conditions. However, the effect of trans-resveratrol on eosinophil activation in relation to allergy has not been investigated. EXPERIMENTAL APPROACH: Human eosinophils were isolated and purified from whole blood and incubated for 16 h with trans-resveratrol. Eosinophil chemotaxis, activation and degranulation, and apoptosis were investigated. The effect of trans-resveratrol on the inhibition of p38 and ERK1/2 activation was examined. KEY RESULTS: Treatment of human eosinophils with trans-resveratrol at concentrations <100 μM for 16 h did not induce eosinophil apoptosis. Similar results were seen after 24 h and 48 h incubations. trans-Resveratrol (<100 μM) significantly inhibited eosinophil peroxidase release after activation with IL-5 (IC(50)=2.9±0.9 μM) or C5a (IC(50)=3.9±0.5 μM) after 5 min priming with cytochalasin B (CB). Similarly, the production of leukotriene C4 after stimulation with calcium ionophore, and eosinophil chemotaxis in response to eotaxin, as well as CD11b upregulation and CD62 L shedding was also significantly reduced by trans-resveratrol, at concentrations above 5 μM. All the activators induced p38 and ERK1/2 phosphorylation maximal at 2 min of activation. trans-Resveratrol potently inhibited p38 and ERK1/2 activation after calcium ionophore and CB and C5a activation. CONCLUSIONS AND IMPLICATIONS: trans-Resveratrol is effective at inhibiting human eosinophil activation and degranulation at concentrations <100 μM, while not inducing apoptosis. This potent anti-inflammatory activity of trans-resveratrol and possibly its metabolites on eosinophils may be worth investigating for the treatment of eosinophil-related allergic diseases.